Electricity storage device

By using an acid-modified polyolefin resin in the sealing portion of the power storage device and providing a specific carbon coating on the surface of the current collector, the short circuit and liquid leakage caused by the peeling of the sealing portion are solved, and the peeling strength of the sealing portion is improved.

CN119923733APending Publication Date: 2025-05-02TOYOTA INDUSTRIES CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380068746.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-27
Filing Date
2023-08-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

When the existing power storage device increases in the confined space, the sealing portion is easily peeled off from the current collector, resulting in a short circuit between the current collectors and a liquid leakage of the liquid electrolyte.

Method used

A sealing portion consisting of an acid-modified polyolefin resin is used, and a carbon coating containing a specific coating adhesive is provided on the bonding portion on the current collector surface to improve the peel strength of the sealing portion.

Benefits of technology

By using an acid-modified polyolefin resin and a carbon coating, the peel strength of the sealing portion is significantly improved, and short circuits between current collectors and liquid leakage of liquid electrolyte are prevented.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119923733A_ABST
    Figure CN119923733A_ABST
Patent Text Reader

Abstract

A power storage device (10) is provided with: a positive electrode (21) in which a positive electrode active material layer (21b) is formed on a first surface (21a1) of a positive electrode current collector (21a); and a sealing part (24) that is adhered to the first surface (21a1) of the positive electrode (21). The sealing part (24) is configured from an acid-modified polyolefin resin. The positive electrode (21) is provided with a carbon coating layer (M) provided on a portion of the first surface (21a1) of the positive electrode current collector (21a), said portion being bonded to the sealing section (24). The carbon coating (M) contains carbon particles and a coating binder. The coating adhesive has an intensity ratio (PCOO / PCH) of a peak indicating a COO structure (PCOO) to a peak indicating a CH structure (PCH) in an IR absorption spectrum measured by an infrared spectrophotometer of 0.5 to 3.3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a power storage device. Background Art

[0002] Patent Document 1 discloses a flat-type power storage device constructed by stacking a plurality of separately manufactured power storage cells in series. The power storage cell comprises a positive electrode having a positive electrode active material layer formed in the center of one surface of a foil-shaped positive electrode current collector; a negative electrode having a negative electrode active material layer formed in the center of one surface of a foil-shaped negative electrode current collector, the negative electrode active material layer being arranged so as to face the positive electrode active material layer; and a separator disposed between the positive and negative electrodes.

[0003] The battery cell further includes a sealing portion disposed between the positive electrode and the negative electrode and disposed on the outer periphery of the positive and negative electrode active material layers. The sealing portion maintains a gap between the positive and negative electrode current collectors to prevent short circuits between the current collectors, and liquid-tightly seals the gap between the positive and negative electrode current collectors, thereby forming a sealed space between the positive and negative electrode current collectors for storing a liquid electrolyte.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2017-16825 Summary of the Invention

[0007] Problems to be solved by the invention

[0008] In conventional power storage devices, when a load is applied to the bond between the current collector and the seal, such as when the internal pressure of a confined space increases, the seal may peel from the current collector. This peeling of the seal can cause a short circuit between the current collectors and leakage of the liquid electrolyte.

[0009] The present inventors have discovered that the peel strength of the sealant is improved by using a sealant composed of an acid-modified polyolefin resin and providing a carbon coating containing a specific coating binder on the surface of the current collector where the sealant adheres.

[0010] Solutions for solving problems

[0011] In one embodiment of the present disclosure, there is provided a storage device comprising: a plurality of electrodes having an active material layer formed on a first surface of a current collector; and a sealing portion disposed between the plurality of electrodes and bonded to the first surface of the current collector. The sealing portion is composed of an acid-modified polyolefin resin. At least one of the plurality of electrodes comprises a carbon coating provided on a bonding portion of the first surface of the current collector to the sealing portion. The carbon coating comprises carbon particles and a coating binder. The coating binder exhibits an IR absorption spectrum at 1680 cm-1 as measured by an infrared spectrophotometer. -1 Above 1720cm -1 Peaks within the range below (P COO ) relative to 1400cm -1 Over 1600cm -1 Peaks within the range below (P CH ) intensity ratio (P COO / P CH ) is greater than or equal to 0.5 and less than or equal to 3.3.

[0012] In another embodiment of the present disclosure, a power storage device is provided, comprising: a first electrode having a first active material layer provided at the center of a first surface of a first current collector; a second electrode having a second active material layer provided at the center of a first surface of the second current collector, the second active material layer being arranged so as to face the first active material layer of the first electrode; a separator arranged between the first active material layer and the second active material layer; and a sealing portion arranged between the first electrode and the second electrode so as to surround the first active material layer and the second active material layer, and bonded to the first surfaces of the first current collector and the second current collector, thereby forming a sealed space for accommodating a liquid electrolyte between the first electrode and the second electrode. The sealing portion is made of an acid-modified polyolefin resin. The first electrode comprises a carbon coating provided at a portion of the first surface of the first current collector that is bonded to the sealing portion. The carbon coating comprises carbon particles and a coating binder. The coating binder exhibits an IR absorption spectrum at 1680 cm-1 as measured by an infrared spectrophotometer. -1 Above 1720cm -1 Peaks within the range below (P COO ) relative to 1400cm -1 Over 1600cm -1 Peaks within the range below (P CH ) intensity ratio (P COO / P CH ) is greater than or equal to 0.5 and less than or equal to 3.3. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a cross-sectional view of the power storage device. DETAILED DESCRIPTION

[0014] Hereinafter, one embodiment of the present disclosure will be described with reference to the accompanying drawings.

[0015] Figure 1 The illustrated power storage device 10 is, for example, a power storage module used in batteries for various vehicles such as forklifts, hybrid vehicles, and electric vehicles. Power storage device 10 is, for example, a secondary battery such as a nickel-metal hydride secondary battery or a lithium-ion secondary battery. Power storage device 10 may also be an electric double-layer capacitor. In this embodiment, a lithium-ion secondary battery is used as an example of power storage device 10.

[0016] <Electrical Storage Device>

[0017] like Figure 1 As shown, the power storage device 10 is configured as a cell stack 30 (laminate) including a plurality of power storage cells 20 stacked (laminated) in a stacking direction. Hereinafter, the stacking direction of the plurality of power storage cells 20 will be referred to simply as the stacking direction. Each power storage cell 20 includes a positive electrode 21, a negative electrode 22, a separator 23, and a sealing portion 24. In this embodiment, one of the positive electrode 21 and the negative electrode 22 corresponds to the first electrode, and the other corresponds to the second electrode.

[0018] The positive electrode 21 includes a positive electrode current collector 21a and a positive electrode active material layer 21b provided on a first surface 21a1 of the positive electrode current collector 21a. In this embodiment, the positive electrode 21, the positive electrode current collector 21a, and the positive electrode active material layer 21b correspond to an electrode, a current collector, and an active material layer, respectively.

[0019] In a plan view (hereinafter referred to as a plan view) viewed from the stacking direction, the positive electrode active material layer 21b is formed in the center of the first surface 21a1 of the positive electrode current collector 21a. The peripheral edge of the first surface 21a1 of the positive electrode current collector 21a in a plan view forms a positive electrode uncoated portion 21c where the positive electrode active material layer 21b is not provided. The positive electrode uncoated portion 21c is arranged so as to surround the positive electrode active material layer 21b in a plan view.

[0020] The negative electrode 22 includes a negative electrode current collector 22a and a negative electrode active material layer 22b provided on a first surface 22a1 of the negative electrode current collector 22a. The negative electrode active material layer 22b is formed in the center of the first surface 22a1 of the negative electrode current collector 22a when viewed from above. The peripheral edge of the first surface 22a1 of the negative electrode current collector 22a when viewed from above forms a negative electrode uncoated portion 22c where the negative electrode active material layer 22b is not provided. The negative electrode uncoated portion 22c is arranged to surround the negative electrode active material layer 22b when viewed from above.

[0021] The positive electrode 21 and the negative electrode 22 are arranged so that the positive electrode active material layer 21b and the negative electrode active material layer 22b face each other in the stacking direction. That is, the relative direction between the positive electrode 21 and the negative electrode 22 coincides with the stacking direction. The negative electrode active material layer 22b is formed slightly larger than the positive electrode active material layer 21b. When viewed from above in the stacking direction, the entire region where the positive electrode active material layer 21b is formed is located within the region where the negative electrode active material layer 22b is formed.

[0022] Here, the positive electrode current collector 21a has a second surface 21a2 located opposite the first surface 21a1, and the negative electrode current collector 22a has a second surface 22a2 located opposite the first surface 22a1. The cell stack 30 has a structure in which a plurality of power storage cells 20 are stacked such that the second surface 21a2 of the positive electrode current collector 21a contacts the second surface 22a2 of the negative electrode current collector 22a. Thus, the plurality of power storage cells 20 constituting the cell stack 30 are connected in series.

[0023] In the cell stack 30, two adjacent storage cells 20 in the stacking direction form a pseudo-bipolar electrode 25, where the positive electrode current collector 21a and the negative electrode current collector 22a in contact with each other are considered as a single current collector. The pseudo-bipolar electrode 25 includes a current collector having a structure in which the positive electrode current collector 21a and the negative electrode current collector 22a are stacked, a positive electrode active material layer 21b formed on one surface of the current collector, and a negative electrode active material layer 22b formed on the other surface of the current collector.

[0024] Alternatively, the positive electrode current collector 21a and the negative electrode current collector 22a may form a bipolar current collector in which the second surface 21a2 of the positive electrode current collector 21a and the second surface 22a2 of the negative electrode current collector 22a are joined. In this case, the positive electrode 21 and the negative electrode 22 form a bipolar electrode 25 having a single bipolar current collector in which the positive electrode current collector 21a and the negative electrode current collector 22a are joined.

[0025] The separator 23 is a member disposed between the positive electrode 21 and the negative electrode 22 , and prevents a short circuit caused by contact between the positive electrode 21 and the negative electrode 22 by isolating the positive electrode 21 and the negative electrode 22 , while allowing charge carriers such as lithium ions to pass therethrough.

[0026] Separator 23 is, for example, a porous sheet or nonwoven fabric containing a polymer that absorbs and retains a liquid electrolyte. Examples of materials constituting separator 23 include polypropylene, polyethylene, polyolefins, and polyesters. Separator 23 can have a single-layer structure or a multi-layer structure. A multi-layer structure can include, for example, an adhesive layer and a ceramic layer serving as a heat-resistant layer.

[0027] The sealing portion 24 is disposed between the first surface 22a1 of the positive electrode current collector 21a of the positive electrode 21 and the first surface 22a1 of the negative electrode current collector 22a of the negative electrode 22, and is disposed on the outer periphery of the positive electrode active material layer 21b and the negative electrode active material layer 22b. The sealing portion 24 is bonded to both the positive electrode current collector 21a and the negative electrode current collector 22a. The sealing portion 24 prevents short circuits between the current collectors by insulating the positive electrode current collector 21a and the negative electrode current collector 22a.

[0028] In a plan view, the sealing portion 24 extends along the periphery of the positive electrode current collector 21a and the negative electrode current collector 22a and is formed into a frame shape surrounding the positive electrode active material layer 21b and the negative electrode active material layer 22b. The sealing portion 24 is arranged between the positive electrode uncoated portion 21c of the first surface 21a1 of the positive electrode current collector 21a and the negative electrode uncoated portion 22c of the first surface 22a1 of the negative electrode current collector 22a.

[0029] A sealed space S surrounded by a frame-shaped seal 24 , the positive electrode 21 , and the negative electrode 22 is formed inside the storage cell 20 . A separator 23 and a liquid electrolyte are accommodated in the sealed space S. The peripheral edge of the separator 23 is embedded in the seal 24 .

[0030] The sealing portion 24 seals the sealed space S between the positive electrode 21 and the negative electrode 22, thereby suppressing the permeation of the liquid electrolyte contained in the sealed space S to the outside. Furthermore, the sealing portion 24 suppresses the intrusion of moisture from the outside of the power storage device 10 into the sealed space S. Furthermore, the sealing portion 24 suppresses the leakage of gas generated from the positive electrode 21 or the negative electrode 22 due to, for example, charge and discharge reactions to the outside of the power storage device 10.

[0031] The seal portion 24 of each power storage cell 20 has an outer peripheral portion 24a that extends outward from the edges of the positive electrode collector 21a and the negative electrode collector 22a. When viewed in the stacking direction, the outer peripheral portion 24a protrudes in a direction perpendicular to the stacking direction, beyond the edges of the positive electrode collector 21a and the negative electrode collector 22a. Adjacent power storage cells 20 in the stacking direction are integrated by bonding the outer peripheral portions 24a of their respective seal portions 24 together. Examples of methods for bonding adjacent seal portions 24 include well-known welding methods such as heat welding, ultrasonic welding, and infrared welding.

[0032] The power storage device 10 includes a pair of current-carrying members, namely a positive current-carrying plate 40 and a negative current-carrying plate 50, arranged in the stacking direction of the cell stack 30 so as to sandwich the cell stack 30. The positive current-carrying plate 40 and the negative current-carrying plate 50 are each made of a material having excellent electrical conductivity.

[0033] The positive electrode current conducting plate 40 is electrically connected to the second surface 21a2 of the positive electrode current collector 21a of the outermost positive electrode 21 at one end in the stacking direction. The negative electrode current conducting plate 50 is electrically connected to the second surface 22a2 of the negative electrode current collector 22a of the outermost negative electrode 22 at the other end in the stacking direction.

[0034] The power storage device 10 is charged and discharged via terminals provided on the positive electrode current plate 40 and the negative electrode current plate 50. For example, the same material as that used to form the positive electrode current collector 21a can be used as the material constituting the positive electrode current plate 40. The positive electrode current plate 40 can also be made of a metal plate thicker than the positive electrode current collector 21a used in the unit stack 30. For example, the same material as that used to form the negative electrode current collector 22a can be used as the material constituting the negative electrode current plate 50. The negative electrode current plate 50 can also be made of a metal plate thicker than the negative electrode current collector 22a used in the unit stack 30.

[0035] Next, the details of the positive electrode current collector 21 a , the negative electrode current collector 22 a , the positive electrode active material layer 21 b , the negative electrode active material layer 22 b , the liquid electrolyte, and the sealing portion 24 will be described.

[0036] <Positive Electrode Collector and Negative Electrode Collector>

[0037] The positive electrode current collector 21a is a chemically inert electrical conductor for allowing current to continue to flow through the positive electrode active material layer 21b during the discharge or charge period of the lithium ion secondary battery. An example of the positive electrode current collector 21a is an aluminum current collector whose surface forming the first surface 21a1 is composed of aluminum. The aluminum current collector can be a single substance composed of aluminum as a whole, or a composite having a portion composed of aluminum and a portion composed of a material other than aluminum. As the above-mentioned single substance, for example, aluminum foil can be listed. As the above-mentioned composite, a multilayer structure in which the layer constituting the first surface 21a1 is an aluminum layer, and a substrate whose surface including the first surface 21a1 is coated with an aluminum film can be listed.

[0038] Examples of materials other than aluminum include metal materials, conductive resin materials, and conductive inorganic materials. Examples of the metal materials include copper, nickel, titanium, and stainless steel (e.g., SUS304, SUS316, SUS301, and SUS304 as specified in JIS G 4305:2015). Examples of the conductive resin materials include conductive polymer materials and resins obtained by adding conductive fillers to non-conductive polymer materials as needed. The aluminum current collector may be in the form of, for example, foil, sheet, or film. The thickness of the aluminum current collector may be, for example, 1 to 100 μm.

[0039] The negative electrode current collector 22 a is a chemically inert electrical conductor for allowing current to continue to flow through the negative electrode active material layer 22 b during discharge or charge of the lithium ion secondary battery.

[0040] An example of the negative electrode current collector 22a is a copper current collector whose surface forming the first surface 22a1 is made of copper. The copper current collector may be a single substance entirely composed of copper, or a composite having a portion composed of copper and a portion composed of a material other than copper. Examples of the single substance include copper foil. Examples of the composite include a multilayer structure in which the layer constituting the first surface 22a1 is a copper layer, and a substrate in which the surface of the first surface 22a1 is coated with a copper film.

[0041] Examples of materials other than copper include metal materials, conductive resin materials, and conductive inorganic materials. Examples of metal materials include aluminum, nickel, titanium, and stainless steel (e.g., SUS304, SUS316, SUS301, and SUS304 as specified in JIS G 4305:2015). Examples of conductive resin materials include conductive polymer materials and resins obtained by adding conductive fillers to non-conductive polymer materials as needed. The copper current collector may be in the form of, for example, foil, sheet, or film. The aluminum current collector may have a thickness of, for example, 1 to 100 μm.

[0042] An example of a preferred combination of the positive electrode current collector 21a and the negative electrode current collector 22a is a case where the positive electrode current collector 21a is composed of aluminum foil as an aluminum current collector, and the negative electrode current collector 22a is composed of copper foil as a copper current collector. Examples of the bipolar current collector include a current collector formed by laminating aluminum foils, a current collector formed by laminating aluminum foil and copper foil, and a current collector formed by plating copper on the surface of aluminum foil.

[0043] Furthermore, the first surface 21 a 1 of the positive electrode current collector 21 a is provided with a carbon coating layer M. The carbon coating layer M will be described in detail later.

[0044] <Positive Electrode Active Material Layer and Negative Electrode Active Material Layer>

[0045] The positive electrode active material layer 21b contains a positive electrode active material that can absorb and release charge carriers such as lithium ions. As the positive electrode active material, it is sufficient to use a material that can be used as a positive electrode active material for a lithium ion secondary battery, such as a lithium composite metal oxide with a layered rock salt structure, a metal oxide with a spinel structure, or a polyanion compound. In addition, two or more positive electrode active materials can also be used in combination. In this embodiment, the positive electrode active material layer 21b contains olivine-type lithium iron phosphate (LiFePO4) as a polyanion compound.

[0046] The negative electrode active material layer 22b can be any single substance, alloy or compound that can absorb and release charge carriers such as lithium ions, and can be used without particular limitation. For example, as the negative electrode active material, lithium (Li), or carbon, metal compounds, elements or compounds that can be alloyed with lithium, etc. can be listed. As carbon, natural graphite, artificial graphite, or hard carbon (difficult to graphitize carbon) or soft carbon (easy to graphitize carbon) can be listed. As artificial graphite, highly oriented graphite, mesophase carbon microbeads, etc. can be listed. As examples of elements that can be alloyed with lithium, silicon and tin can be listed. In the present embodiment, the negative electrode active material layer 22b contains graphite as a carbon-based material.

[0047] The positive electrode active material layer 21b and the negative electrode active material layer 22b (hereinafter also referred to as the active material layer) may further include a conductive additive for improving conductivity, a binder, an electrolyte (polymer matrix, ion-conductive polymer, liquid electrolyte, etc.), an electrolyte supporting salt (lithium salt) for improving ion conductivity, etc., as needed. The components contained in the active material layer, the mixing ratio of the components, and the thickness of the active material layer are not particularly limited and can be appropriately referred to the conventional knowledge of lithium-ion secondary batteries.

[0048] The conductive additive is added to improve the conductivity of the positive electrode 21 or the negative electrode 22. Examples of the conductive additive include acetylene black, carbon black, and graphite.

[0049] Examples of the binder include fluorine-containing resins such as polyvinylidene fluoride, polytetrafluoroethylene, and fluororubber, thermoplastic resins such as polypropylene and polyethylene, imide resins such as polyimide and polyamide-imide, alkoxysilyl-containing resins, acrylic resins such as poly(meth)acrylic acid, styrene-butadiene rubber, carboxymethyl cellulose, alginates such as sodium alginate and ammonium alginate, water-soluble cellulose ester crosslinks, and starch-acrylic acid graft polymers. These binders can be used alone or in combination. Examples of the solvent or dispersion medium include water and N-methyl-2-pyrrolidone.

[0050] The method for forming the active material layer on the surface of the positive electrode current collector 21 a and the negative electrode current collector 22 a is not particularly limited, and a conventionally known method such as a roll coating method can be used.

[0051] In order to improve the thermal stability of the positive electrode 21 or the negative electrode 22 , the above-mentioned heat-resistant layer may be provided on the surface of the active material layer.

[0052] The weight per unit area of ​​the active material layer is not particularly limited and can be appropriately determined by reference to conventional knowledge regarding lithium-ion secondary batteries. However, from the perspective of increasing the energy density of the storage cell 20, it is preferable to increase the weight per unit area of ​​the active material layer. The weight per unit area of ​​the positive electrode active material layer 21b is, for example, 55 to 90 mg / cm 2 , preferably 60 mg / cm 2 More than 70 mg / cm 2 The weight per unit area of ​​the negative electrode active material layer 22b is, for example, 25 to 45 mg / cm 2 , preferably 30 mg / cm 2 above.

[0053] <Seal section>

[0054] The sealing portion 24 is composed of an acid-modified polyolefin resin. Examples of the acid-modified polyolefin resin include acid-modified polyethylene, acid-modified polypropylene, acid-modified isoprene, and acid-modified polybutene. Examples of the acid-modified group include carboxylic acid groups, maleic acid groups, and maleic anhydride groups. The acid-modified polyolefin resin comprising the sealing portion 24 may be a single type or a combination of two or more types. The acid-modified polyolefin resin comprising the sealing portion 24 may be a thermoplastic resin or a thermosetting resin.

[0055] The melting point Tm1 of the acid-modified polyolefin-based resin constituting the sealing portion 24 is, for example, 90° C. or higher and 170° C. or lower.

[0056] The thickness of the sealing portion 24 is preferably 50 μm to 1000 μm, more preferably 100 μm to 800 μm. The thickness of the sealing portion 24 refers to the thickness of the portion located between the first surface 21 a 1 of the positive electrode current collector 21 a and the first surface 22 a 1 of the negative electrode current collector 22 a .

[0057] The sealing portion 24 is bonded to the first surface 21a1 of the positive electrode current collector 21a, more specifically, to the carbon coating layer M provided on the first surface 21a1. The sealing portion 24 is also bonded to the first surface 22a1 of the negative electrode current collector 22a.

[0058] Liquid electrolyte

[0059] The liquid electrolyte comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. As the electrolyte salt, known lithium salts such as LiClO4, LiAsF6, LiPF6, LiBF4, LiCF3SO3, LiN(FSO2)2, and LiN(CF3SO2)2 can be used. In addition, known solvents such as cyclic carbonates, cyclic esters, chain carbonates, chain esters, and ethers can be used as the non-aqueous solvent. In addition, two or more of these known solvent materials can be combined for use.

[0060] In addition, an example of a liquid electrolyte includes a fluorine-containing metal salt as an electrolyte salt. Examples of the fluorine-containing metal salt include fluorine-containing lithium salts such as LiPF6, LiBF4, and LiAsF6. When the fluorine-containing metal salt is included, the proportion of the fluorine-containing metal salt in the electrolyte salt is, for example, 50% by mass or greater.

[0061] Carbon coating

[0062] Next, the carbon coating layer M provided on the first surface 21 a 1 of the positive electrode current collector 21 a will be described.

[0063] In this embodiment, the carbon coating M is provided on the entire first surface 21a1 of the positive electrode current collector 21a. Therefore, the first surface 21a1 of the positive electrode current collector 21a is bonded to the sealing portion 24 via the carbon coating M. In other words, the sealing portion 24 is bonded to the carbon coating M provided on the first surface 21a1 of the positive electrode current collector 21a.

[0064] The carbon coating M comprises carbon particles and a coating binder.

[0065] As the carbon particles, known carbon materials used for carbon coatings such as graphite and acetylene black can be used. The content of the carbon particles in the carbon coating M is, for example, 13% by mass or more and 90% by mass or less.

[0066] The coating binder has a structure represented by "-COO-" (hereinafter referred to as COO structure) and a structure represented by "-CH" (hereinafter referred to as CH structure) in the chemical formula, and is composed of a material in which the abundance ratio of these structures is within a specific range.

[0067] Specifically, the coating adhesive has a peak indicating a COO structure and a peak indicating a CH structure in the infrared (IR) absorption spectrum measured by an infrared spectrophotometer, and the intensity ratio of these two peaks is a specific ratio. The peak indicating the COO structure appears at 1680 cm in the above IR absorption spectrum. -1 Above 1720cm -1 The peak indicating the CH structure appears at 1400 cm in the above IR absorption spectrum. -1 Over 1600cm-1 The peaks in the following range.

[0068] The peak representing the COO structure (P COO ) relative to the peak representing the CH structure (P CH ) intensity ratio (P COO / P CH ) is 0.5 or more and 3.3 or less. By using a coating adhesive having the strength ratio within the above range, it is possible to suppress a decrease in the peel strength of the sealing portion 24 due to the passage of time.

[0069] The intensity used in the calculation of the above intensity ratio is the transmission absorbance A* (=log(1 / R)) calculated based on the measured transmission reflectance R, and is the value obtained by subtracting the background from the transmission absorbance A*. CH ) and peak (P COO ) means the intensity of the peak apex.

[0070] Examples of the material constituting the coating binder include acrylic resins and carboxyl-modified styrene-butadiene rubber. The material constituting the coating binder is preferably an acrylic resin.

[0071] Examples of acrylic resins include homopolymers of acrylic monomers such as acrylic acid, methacrylic acid, and (meth)acrylic acid esters, and (meth)acrylic acid copolymers containing these acrylic monomers. In the present embodiment, (meth)acrylic acid means acrylic acid or methacrylic acid.

[0072] Examples of the (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, and isobutyl (meth)acrylate.

[0073] In the (meth)acrylic acid copolymers, other comonomers copolymerized with the acrylic monomers include α-olefins, styrene, α-methylstyrene, vinyltoluene, acrylonitrile, methacrylonitrile, and vinyl acetate. These comonomers can be present in the acrylic resin as random copolymers, graft copolymers, or block copolymers. Examples of the (meth)acrylic acid copolymers include silicon-modified acrylic styrene resins, carboxyl-modified acrylic styrene resins, and hydroxyl-modified acrylic resins.

[0074] The material constituting the coating adhesive may be one or a combination of two or more. In addition, when the coating adhesive is a mixture of two or more of the above materials, the coating adhesive as a whole may be adjusted in such a manner that the above strength ratio falls within the above range.

[0075] The glass transition temperature Tg2 of the coating adhesive is, for example, 0°C to 150°C. When the sealing portion 24 is bonded by heat fusion, the sealing member forming the sealing portion 24 is preferably heated to a temperature exceeding the glass transition temperature Tg2 of the coating adhesive and at a temperature above the melting point Tm1 of the acid-modified polyolefin resin constituting the sealing portion 24. In this case, the heating for bonding the sealing portion 24 softens the coating adhesive contained in the carbon coating M, thereby facilitating compatibility between the coating adhesive and the sealing portion 24. Therefore, the glass transition temperature Tg2 of the coating adhesive is preferably lower than the melting point Tm1 of the acid-modified polyolefin resin constituting the sealing portion 24 (Tg2 < Tm1). The difference between the melting point Tm1 of the acid-modified polyolefin resin and the glass transition temperature Tg2 of the coating adhesive (melting point Tm1 - Tg2) is, for example, 5°C to 100°C.

[0076] The thickness of the carbon coating layer M is, for example, not less than 0.1 μm and not more than 5 μm, and preferably not less than 0.5 μm and not more than 2 μm.

[0077] The carbon coating layer may contain other components such as a dispersant. Examples of the dispersant include carboxyethyl cellulose.

[0078] Next, a method for manufacturing the power storage device 10 according to the present embodiment will be described.

[0079] The power storage device 10 is manufactured by sequentially performing an electrode forming step, a power storage cell forming step, and a cell stack forming step. Here, as an example, a case where the positive electrode current collector 21a is formed of aluminum foil and the negative electrode current collector 22a is formed of copper foil will be described.

[0080] <Electrode Formation Process>

[0081] The electrode forming step includes a positive electrode forming step of forming the positive electrode 21 and a negative electrode forming step of forming the negative electrode 22 .

[0082] In the positive electrode formation process, a carbon coating M is first formed on the entire first surface 21a1 of the aluminum foil serving as the positive electrode current collector 21a. Prior to forming the carbon coating M, the first surface 21a1 of the aluminum foil is subjected to a corona discharge treatment. The corona discharge treatment forms hydrophilic groups (OH groups) on the first surface 21a1 of the aluminum foil. The carbon coating M can be formed using known methods for forming coatings, such as solution-based processes and vapor deposition processes.

[0083] An example of a solution-based process is described below. First, a carbon paste is prepared by kneading carbon particles, a coating binder, and an aqueous solvent. A coating film is formed by adhering the carbon paste to the entire first surface 21a1 of the positive electrode current collector 21a in a manner having a predetermined thickness. A carbon coating M is formed by drying and curing the formed coating film. As a process for curing the coating film of the carbon paste, for example, the following process can be cited: after drying to volatilize the solvent, heating to a temperature above the glass transition temperature Tg2 of the coating binder, and then cooling to solidify it. As aqueous solvents used in the carbon paste, for example, water and mixed solvents of water and organic solvents can be cited. As organic solvents used in the mixed solvent, for example, N-methyl-2-pyrrolidone (NMP) can be cited.

[0084] In addition, when forming a bipolar electrode 25 having a bipolar collector, instead of the aluminum foil as the positive electrode collector 21a, a collector formed by laminating aluminum foils to each other, a collector formed by laminating aluminum foil and copper foil, a collector with copper plated on the surface of aluminum foil, etc. are used.

[0085] Next, the positive electrode composite material, which will become the positive electrode active material layer 21b by curing, is attached to the center portion of the first surface 21a1 of the aluminum foil having the carbon coating M formed thereon. Thereafter, a curing treatment corresponding to the positive electrode composite material is performed to form the positive electrode active material layer 21b.

[0086] The negative electrode forming process is not particularly limited, and a known method used in forming the negative electrode 22 having the negative electrode current collector 22a and the negative electrode active material layer 22b can be used. For example, the negative electrode composite material, which becomes the negative electrode active material layer 22b by curing, is attached to the first surface 22a1 of the copper foil serving as the negative electrode current collector 22a to a predetermined thickness, and then a curing treatment corresponding to the negative electrode composite material is performed to form the negative electrode 22.

[0087] <Electricity Storage Cell Formation Process>

[0088] In the battery cell formation process, the positive electrode 21 and the negative electrode 22 are first arranged so that the positive electrode active material layer 21b and the negative electrode active material layer 22b face each other in the stacking direction, with the separator 23 sandwiched therebetween. Furthermore, a sealant, serving as the seal portion 24, is arranged between the positive electrode 21 and the negative electrode 22, and on the outer periphery of the positive electrode collector 21a and the negative electrode collector 22a. The sealant is formed by cutting a resin sheet made of an acid-modified polyolefin resin into a shape identical to the top view shape of the seal portion 24. The sealant is arranged so as to contact the carbon coating layer M on the first surface 21a1 of the positive electrode collector 21a.

[0089] Thereafter, the positive electrode 21, the negative electrode 22, and the separator 23 are bonded to the seal by welding, thereby forming an assembly in which the positive electrode 21, the negative electrode 22, the separator 23, and the seal 24 are integrated. Examples of methods for bonding the seal include well-known welding methods such as heat welding, ultrasonic welding, and infrared welding.

[0090] When forming the seal portion 24 by heat welding, a treatment such as heating the seal to a temperature equal to or higher than the melting point Tm1 of the acid-modified polyolefin resin constituting the seal and then cooling the seal to solidify the seal can be employed. In this case, if the glass transition temperature Tg2 of the coating adhesive is lower than the melting point Tm1 of the acid-modified polyolefin resin, the coating adhesive also softens, thereby facilitating compatibility between the coating adhesive and the acid-modified polyolefin resin.

[0091] Next, a liquid electrolyte is injected into the sealed space S inside the assembly through an injection port provided in a portion of the sealing portion 24 , and the injection port is sealed. Thus, the electricity storage cell 20 is formed.

[0092] <Cell Stack Formation Process>

[0093] In the cell stack formation step, multiple storage cells 20 are first stacked so that the second surface 21a2 of the positive electrode current collector 21a faces the second surface 22a2 of the negative electrode current collector 22a. Subsequently, the plurality of storage cells 20 are integrated by bonding the outer peripheral portions 24a of the seals 24 of adjacent storage cells 20 in the stacking direction.

[0094] Next, the positive electrode current conducting plate 40 is superimposed on the second surface 21a2 of the positive electrode current collector 21a of the positive electrode 21, which is positioned outermost at one end in the stacking direction, and is fixed thereto in an electrically connected state. Similarly, the negative electrode current conducting plate 50 is superimposed on the second surface 22a2 of the negative electrode current collector 22a of the negative electrode 22, which is positioned outermost at the other end in the stacking direction, and is fixed thereto in an electrically connected state.

[0095] <Function>

[0096] Next, the operation of this embodiment will be described.

[0097] In the electricity storage device 10 of this embodiment, a carbon coating layer M is provided entirely on the first surface 21a1 of the positive electrode current collector 21a. Furthermore, a sealing portion 24 composed of an acid-modified polyolefin-based resin is bonded to the carbon coating layer M provided on the first surface 21a1 of the positive electrode current collector 21a. The coating binder contained in the carbon coating layer M has a COO structure and a CH structure, and is composed of a material in which the abundance ratio of these structures is within the specific range described above.

[0098] In the case of this structure, the first surface 21a1 of the positive electrode current collector 21a is bonded to the coating binder contained in the carbon coating M. It is considered that the bond is either or both of an ester bond and a hydrogen bond. The above-mentioned ester bond is a bonding structure (-COOMe) in which the hydroxyl group (Me-OH) of the first surface 21a1 of the positive electrode current collector 21a is ester-bonded with the carboxyl group (-COOH) of the coating binder. "Me" means the metal constituting the collector. The above-mentioned hydrogen bond is a bonding structure in which the hydroxyl group (Me-OH) of the first surface 21a1 of the positive electrode current collector 21a is hydrogen-bonded with either or both of the hydroxyl group and the carboxyl group of the substance constituting the carbon coating M. The above-mentioned hydroxyl group is either or both of the hydroxyl group (C-OH) on the surface of the carbon particles and the hydroxyl group (C-OH) of the coating binder. The above-mentioned carboxyl group is the carboxyl group (-COOH) of the coating binder.

[0099] In addition, at the interface between the sealing portion 24 and the carbon coating M, the acid-modified polyolefin resin serving as the sealing portion 24 is bonded to the carbon particles contained in the carbon coating M. This bond is considered to be either or both of an ester bond and a hydrogen bond. The ester bond is a bonding structure (-COOC) formed by ester bonding of the hydroxyl group (C-OH) on the surface of the carbon particle and the carboxyl group (-COOH) of the acid-modified polyolefin resin. The hydrogen bond is a bonding structure formed by hydrogen bonding of either or both of the hydroxyl group and the carboxyl group (-COOH) of the substance constituting the carbon coating M and the carboxyl group (-COOH) of the acid-modified polyolefin resin. The hydroxyl group is either or both of the hydroxyl group (C-OH) on the surface of the carbon particle and the hydroxyl group (C-OH) of the coating binder. The carboxyl group is the carboxyl group (-COOH) of the coating binder. By forming the above-described bonding structure at the interface between the positive electrode current collector 21 a and the carbon coating M and at the interface between the sealing portion 24 and the carbon coating M, the sealing portion 24 is bonded to the first surface 21 a 1 of the positive electrode current collector 21 a via the carbon coating M.

[0100] Furthermore, since the ratio of COO structures to CH structures in the coating binder is within the aforementioned specific range, the coating binder has an improved affinity for the acid-modified polyolefin resin constituting the sealing portion 24. As a result, at the interface between the sealing portion 24 and the carbon coating layer 24, the coating binder and the acid-modified polyolefin resin are compatible and in close contact.

[0101] Thus, according to the configuration of this embodiment, a bonding structure is formed at the interface between the first surface 21a1 of the positive electrode current collector 21a and the carbon coating layer M, and at the interface between the sealing portion 24 and the carbon coating layer M. In addition, the coating binder contained in the carbon coating layer M is compatible with and closely adheres to the sealing portion 24, resulting in an improvement in the peel strength of the sealing portion 24 relative to the positive electrode current collector 21a.

[0102] Furthermore, in the above-described configuration, in which the first surface 21a1 of the positive electrode current collector 21a and the carbon coating layer M are formed, and the carbon coating layer M is tightly bonded to the sealing portion 24, contact between the liquid electrolyte and the first surface 21a1 of the positive electrode current collector 21a can be suppressed. Furthermore, since the carbon coating layer M acts as a barrier that prevents the liquid electrolyte from penetrating the first surface 21a1 of the positive electrode current collector 21a, this also prevents contact between the liquid electrolyte and the first surface 21a1 of the positive electrode current collector 21a. This can thereby suppress a decrease in the peel strength of the sealing portion 24 relative to the positive electrode current collector 21a.

[0103] In more detail, in conventional power storage devices, for example, when using a liquid electrolyte containing LiPF6 as an electrolyte salt and a seal formed of an acid-modified polyolefin resin, the peel strength of the seal may decrease over time. This decrease in the peel strength of the seal is believed to be caused by hydrofluoric acid (HF) derived from the LiPF6. LiPF6, for example, generates hydrofluoric acid by reacting with water (H2O) contained in the liquid electrolyte.

[0104] In the case of an existing structure in which the above-mentioned sealing portion is bonded to the surface of the collector, a bonding structure (-COOMe) is formed in which a hydroxyl group (M-OH) on the surface of the collector and a carboxyl group (-COOH) of an acid-modified polyolefin resin as a sealing portion are ester-bonded. Based on this bonding structure (-COOMe), a sealing portion is bonded to the surface of the collector. Hydrofluoric acid derived from LiPF6 destroys the bonding structure (-COOM) formed between the above-mentioned sealing portion and the collector. Thus, the peel strength of the sealing portion relative to the collector is reduced. Moreover, hydrofluoric acid fluorinates the surface of the collector (MeF). Since the fluorinated portion of the collector surface cannot form a bonding structure (-COOMe) again between the sealing portion, the peel strength of the sealing portion is maintained. As a result, over time, the peel strength of the sealing portion is reduced. It is believed that these phenomena also occur when a liquid electrolyte containing a fluorine-containing metal salt other than LiPF6 is used as an electrolyte salt.

[0105] According to this embodiment, as described above, contact between the liquid electrolyte and the first surface 21a1 of the positive electrode current collector 21a can be suppressed. Therefore, the bond structure formed at the interface between the first surface 21a1 of the positive electrode current collector 21a and the carbon coating layer M is maintained, and fluorination of the first surface 21a1 of the positive electrode current collector 21a is suppressed. As a result, a decrease in the peel strength of the sealing portion 24 over time is suppressed.

[0106] Effects

[0107] According to this embodiment, the following effects can be obtained.

[0108] (1) The power storage device 10 comprises: a positive electrode 21 having a positive electrode active material layer 21b formed on a first surface 21a1 of a positive electrode current collector 21a; and a sealing portion 24 bonded to the first surface 21a1 of the positive electrode 21. The sealing portion 24 is made of an acid-modified polyolefin resin. The positive electrode 21 comprises a carbon coating M provided on a bonding portion of the first surface 21a1 of the positive electrode current collector 21a to the sealing portion 24. The carbon coating M comprises carbon particles and a coating binder. The coating binder has a peak (P COO ) relative to the peak representing the CH structure (P CH ) intensity ratio (P COO / P CH ) is greater than or equal to 0.5 and less than or equal to 3.3.

[0109] According to the above configuration, a bonding structure is formed at the interface between the first surface 21a1 of the positive electrode current collector 21a and the carbon coating layer M, and at the interface between the sealing portion 24 and the carbon coating layer M. In addition, the coating binder contained in the carbon coating layer M is compatible with and closely adheres to the sealing portion 24, resulting in an improvement in the peel strength of the sealing portion 24 relative to the positive electrode current collector 21a.

[0110] (2) The coating binder contains an acrylic resin.

[0111] According to the above configuration, the effect of (1) can be more significantly obtained.

[0112] (3) The carbon coating layer M is provided on the entire first surface 21 a 1 of the positive electrode current collector 21 a .

[0113] According to the above configuration, the process of forming the carbon coating layer M can be simplified compared to a configuration in which the carbon coating layer M is provided on a portion of the first surface 21 a 1 of the positive electrode current collector 21 a .

[0114] (4) The power storage device 10 includes a bipolar electrode 25 having a bipolar current collector. The bipolar current collector is formed by bonding a positive electrode current collector 21a (first current collector) having a first surface 21a1 and a second surface 21a2 located opposite the first surface 21a1, and a negative electrode current collector 22a (second current collector) having a first surface 22a1 and a second surface 22a2 located opposite the first surface 22a1, with the second surface bonded to each other. A positive electrode active material layer 21b (first active material layer) is formed on the first surface 21a1 of the positive electrode current collector 21a. A negative electrode active material layer 22b (second active material layer) is formed on the first surface 22a1 of the negative electrode current collector 22a.

[0115] According to the above configuration, in the electricity storage device 10 including the bipolar electrode 25 , the peel strength of the sealing portion 24 can be improved.

[0116] (6) The electricity storage device 10 includes a liquid electrolyte containing a fluorine-containing metal salt.

[0117] Fluorine-containing metal salts contained in the liquid electrolyte may sometimes cause a decrease in the peel strength of the sealing portion 24. Therefore, it is particularly effective to improve the peel strength of the sealing portion 24 through the effect of (1) above. In addition, it is possible to suppress the decrease in the peel strength of the sealing portion 24 due to the passage of time.

[0118] In addition, this embodiment can be implemented by the following modifications: This embodiment and the following modifications can be implemented in combination with each other within the scope of no technical contradiction.

[0119] The carbon coating M only needs to be provided on at least a portion of the first surface 21a1 of the positive electrode current collector 21a in contact with the sealing portion 24. For example, the portion of the first surface 21a1 of the positive electrode current collector 21a in contact with the sealing portion 24 may partially include a portion not provided with the carbon coating M. However, it is preferred that the carbon coating M be formed in a ring shape surrounding the sealed space S in the portion of the first surface 21a1 of the positive electrode current collector 21a in contact with the sealing portion 24 when viewed from above. Furthermore, the portion of the first surface 21a1 of the positive electrode current collector 21a not in contact with the sealing portion 24 may partially or entirely include a portion not provided with the carbon coating M.

[0120] The first surface 22a1 of the negative electrode current collector 22a may be provided with a carbon coating M instead of the first surface 21a1 of the positive electrode current collector 21a. Alternatively, the carbon coating M may be provided on both the first surface 21a1 of the positive electrode current collector 21a and the first surface 22a1 of the negative electrode current collector 22a.

[0121] The top-view shape of the positive electrode current collector 21a and the positive electrode active material layer 21b is not particularly limited. They may be polygonal, such as a rectangle, or circular or elliptical. The same applies to the negative electrode current collector 22a and the negative electrode active material layer 22b.

[0122] The shape of the sealing portion 24 in plan view is not particularly limited, and may be a polygonal shape such as a rectangle, or may be a circle or an ellipse.

[0123] A conductive layer in close contact with the positive electrode collector 21a may be disposed between the positive electrode current plate 40 and the positive electrode current collector 21a to ensure good conductive contact between the two components. Examples of the conductive layer include a layer containing carbon such as acetylene black or graphite, a plating layer containing Au, or other materials, and other layers having a lower hardness than the positive electrode collector 21a. A similar conductive layer may also be disposed between the negative electrode current plate 50 and the negative electrode current collector 22a.

[0124] There is no particular limitation on the number of electric storage cells 20 constituting the electric storage device 10. The number of electric storage cells 20 constituting the electric storage device 10 may be one.

[0125] A positive electrode active material layer 21b or a negative electrode active material layer 22b may be provided on the second surface 21a2 of the positive electrode current collector 21a. Alternatively, a positive electrode active material layer 21b or a negative electrode active material layer 22b may be provided on the second surface 22a2 of the negative electrode current collector 22a.

[0126] The power storage device 10 may also include a restraining member for restraining the cell stack 30. The restraining member applies a restraining load to a region where the power storage cells 20 face each other in the stacking direction of the cell stack 30, particularly to a region where the positive electrode active material layer 21 b and the negative electrode active material layer 22 b overlap when viewed from above.

[0127] The specific configuration of the restraining member is not particularly limited, as long as it can impart a restraining load to the unit stack 30. Examples of restraining members include a plate-shaped restraining plate and a fastening member, wherein the plate-shaped restraining plates are arranged at both ends of the unit stack 30 in the stacking direction so as to clamp the unit stack 30, and the fastening member comprises a bolt and nut that fasten the restraining plates together. With this restraining member configuration, the fastening member applies a force to the restraining plates toward each other, thereby imparting a restraining load in the stacking direction to the unit stack 30.

[0128] Example

[0129] Hereinafter, examples in which the above-mentioned embodiment is further concretely described will be described.

[0130] <IR Absorption Spectrum Measurement of Coating Adhesives>

[0131] A test piece coated with each of the commercially available resins 1 to 6 shown in Table 1 was obtained by applying the same to an aluminum foil. SBR in Table 1 means styrene-butadiene rubber.

[0132] The IR absorption spectrum of each test piece obtained was measured at 25°C using an infrared spectrophotometer (microscopic reflection method). The measured transmittance reflectance R was used to calculate the transmittance absorbance A* (=log(1 / R)), and a wave number (cm -1 ) as the horizontal axis and the transmission absorbance A* as the vertical axis. Based on the created coordinate graph, the 1680cm -1 Above 1720cm -1 Peaks within the range below (P COO ) intensity, i.e., the transmission absorbance A*, and 1400 cm-1 Over 1600cm -1 Peaks within the range below (P CH ) intensity is the transmission absorbance A*. Then, the peak (P COO ) relative to the peak (P CH ) intensity ratio (P COO / P CH ). These results are shown in Table 1. In addition, the peak (P COO ) and peak (P CH ) intensity uses the value obtained by subtracting the background from the transmission absorbance A*.

[0133] [Table 1]

[0134]

[0135] Preparation of Carbon Paste

[0136] A carbon paste was prepared by kneading carbon particles, a coating binder, carboxyethyl cellulose (CMC), and water. Acetylene black was used as the carbon particles. Any of Resins 1 to 6 was used as the coating binder. The mass ratio of the solid components in the carbon paste was set to 50:37.5:12.5 (carbon particles: coating binder: CMC). The solvent content in the carbon paste was set to an amount that resulted in a solids content of 85% by mass.

[0137] <Preparation of Examples 1 to 4 and Comparative Examples 1 to 3>

[0138] A 30 μm thick aluminum foil was prepared and one side of the foil was hydrophilized by corona discharge treatment. A coating film was formed by applying a carbon paste containing Resin 1 to the entire hydrophilized surface of the aluminum foil. The resulting coating film was dried. The sheet was then heated at 150°C for 10 seconds and then cooled to form a 1 μm thick carbon coating. The resulting sheet was used as the sheet for Example 1.

[0139] Sheets of Examples 2 to 4 were obtained by the same method as in Example 1, except that the carbon paste using Resin 1 was replaced with carbon paste using Resins 2, 4, and 5. Sheets of Comparative Examples 1 and 2 were obtained by the same method as in Example 1, except that the carbon paste using Resin 1 was replaced with carbon paste using Resins 3 and 6.

[0140] <Peel test>

[0141] A rectangular current collector measuring 10 mm in length and 50 cm in width was cut from the sheet of Example 1. Separately, a rectangular seal measuring 10 mm in length and 50 mm in width was prepared. A 150 μm thick, acid-modified polyethylene sheet with a melting point Tm1 of 120°C was used as the seal. The seal was laminated onto the carbon-coated surface of the current collector, with the ends aligned, to produce a laminate.

[0142] Next, the laminate was heated at 150°C for 10 seconds using an impulse sealer and then cooled to produce a test sample in which the current collector and the seal were bonded. A 90-degree peel test was performed on the resulting test sample at a tensile speed of 10 mm / min and a temperature of 60°C. The peel strength of the test sample was calculated by dividing the strength measured by the line width of 10 mm. The results are shown in Table 2.

[0143] The same peeling test as above was performed by replacing the sheet of Example 1 with the sheets of Examples 2 to 4 and Comparative Examples 1 and 2. Table 2 shows the results.

[0144] [Table 2]

[0145]

[0146] As shown in Table 2, the intensity ratio (P COO / P CH ) in the range of 0.5 or more and 3.3 or less and the coating adhesives of each embodiment using the strength ratio (P COO / P CH ) is less than 0.5, the peeling strength is higher than that of Comparative Example 1. The peeling in each example is not the interface failure at the interface between the aluminum foil and the carbon coating, or at the interface between the carbon coating and the seal, but the cohesive failure within the carbon coating layer. This result shows that the aluminum foil and the seal are firmly bonded via the carbon coating. In addition, when using the strength ratio (P COO / P CH In Comparative Example 2, in which the coating binder had a viscosity exceeding 3.3, the sheet was not adhered to the carbon coating layer.

[0147] TEM-EELS (transmission electron microscopy-electron energy loss spectroscopy) analysis of the structure of the interface between the seal and the carbon coating was also performed on the sample from Example 1 before the immersion treatment. The results showed that at this interface, multiple gradient regions were observed, with the carbon coating gradually decreasing in the coating binder and the acid-modified polyolefin resin constituting the seal gradually increasing in the coating binder toward the seal. This result indicates that the coating binder in the carbon coating and the acid-modified polyolefin resin constituting the seal are compatible at this interface.

Claims

1. A power storage device comprising: a plurality of electrodes having an active material layer formed on a first surface of a current collector; and a sealing portion, which is disposed between the plurality of electrodes and bonded to the first surface of the current collector, The power storage device is characterized in that The sealing part is composed of an acid-modified polyolefin resin. At least one of the plurality of electrodes includes a carbon coating provided on a portion of the first surface of the current collector that is bonded to the sealing portion. The carbon coating comprises carbon particles and a coating binder, In the IR absorption spectrum of the coating binder measured by an infrared spectrophotometer, 1680 cm -1 Above and 1720cm -1 The peaks in the range below (P COO ) relative to 1400cm -1 Over 1600cm -1 The peaks in the range below (P CH ) intensity ratio (P COO / P CH ) is greater than 0.5 and less than 3.

3.

2. The power storage device according to claim 1, wherein The coating binder comprises an acrylic resin.

3. The power storage device according to claim 1 or 2, wherein: The carbon coating layer is provided on the entire first surface of the current collector.

4. The power storage device according to any one of claims 1 to 3, wherein: The first side of the current collector is composed of aluminum.

5. The power storage device according to any one of claims 1 to 4, wherein: The electrode is a bipolar electrode, The current collector is a bipolar current collector in which a first current collector having a first surface and a second surface located opposite to the first surface and a second current collector having a first surface and a second surface located opposite to the first surface are bonded to each other at the second surface. A first active material layer as the active material layer is formed on the first surface of the first current collector. A second active material layer serving as the active material layer is formed on the first surface of the second current collector.

6. The power storage device according to claim 5, wherein: The first surface of the first current collector is made of aluminum, The first side of the second current collector is made of copper.

7. The power storage device according to claim 5 or 6, wherein: In the bipolar electrode, the carbon coating layer is provided on portions of both the first surface of the first current collector and the second surface of the second current collector that are bonded to the sealing portion.

8. The power storage device according to any one of claims 1 to 7, wherein: A liquid electrolyte is provided between the plurality of electrodes, The liquid electrolyte includes a fluorine-containing metal salt.

9. An electric storage device, characterized in that: The invention comprises: a first electrode having a first active material layer disposed at a central portion of a first surface of a first current collector; a second electrode having a second active material layer disposed at a central portion of a first surface of a second current collector, the second active material layer being disposed in a manner such that the second active material layer is opposite to the first active material layer of the first electrode; and a separator disposed between the first active material layer and the second active material layer; and a sealing portion, which is arranged between the first electrode and the second electrode in a manner surrounding the first active material layer and the second active material layer, and is bonded to each first surface of the first current collector and the second current collector, so as to form a closed space for accommodating a liquid electrolyte between the first electrode and the second electrode, the sealing portion is composed of an acid-modified polyolefin resin, the first electrode has a carbon coating provided on a bonding portion of the first surface of the first current collector to the sealing portion, the carbon coating comprising carbon particles and a coating binder, and the coating binder has an IR absorption spectrum measured by an infrared spectrophotometer at 1680cm -1 Above and 1720cm -1 The peaks in the range below (P COO ) relative to 1400cm -1 Over 1600cm -1 The peaks in the range below (P CH ) intensity ratio (P COO / P CH ) is greater than 0.5 and less than 3.

3.

10. The power storage device according to claim 9, wherein: The carbon coating layer is provided on both the first surface of the first current collector and the first surface of the second current collector at the bonding portion with the sealing portion.

Citation Information

Patent Citations

  • Secondary battery and method for manufacturing the same

    JP2017016825A